Synergistic antimicrobial properties of nanoencapsulated clove oil and thymol against oral bacteria - Lee, Ji-Soo (Food Sci Biotechnol, 2020)
This study aimed to improve the antimicrobial activity of natural extracts against oral bacteria by synergistic combination and nanoencapsulation. Among five natural antimicrobials: clove oil, thymol, naringin, naringenin, and licorice, clove oil and thymol were selected by comparing the antimicrobial activities against Streptococcus mutans and Streptococcus sobrinus before and after nanoencapsulation. The combination of clove oil and thymol (CLTY) was nanoencapsulated using chitosan and poly-γ-glutamic acid. While free CLTY showed additive and synergistic antimicrobial activity against S. mutans and S. sobrinus, respectively, CLTY nanoparticles (NPs) exhibited synergistic activity against both strains in a time-kill kinetic assay. CLTY NPs significantly decreased the growth of salivary S. mutans during testing, compared with free CLTY in the mouth rinse test. These results indicate that nanoencapsulation can significantly increase the synergistic antimicrobial activity of CLTY and maintain its antimicrobial activity in oral cavities for a longer time.